Wild Kratts. A creature Christmas [videorecording (DVD)]. - Kratt, Martin; Kratt, Chris (Wild Kratts (Television program), 2016)
It's Christmas time and the Wild Kratts are taking a break from creature adventuring to celebrate. They are beginning to open their presents when the Wild Kratts alarm sounds. The villains, Zach Varmitech, Gaston Gourmand, and Donita Donata are kidnapping all the baby animals to turn them into Christmas ornaments! Christmas will have to wait as the Wild Kratts spring into action to save their friends and get them home for Christmas.